FTY720 inhibits mesothelioma growth in vitro and in a syngeneic mouse model - Szymiczek, Agata (J Transl Med, 2017)
BACKGROUND: Malignant mesothelioma (MM) is a very aggressive type of cancer, with a dismal prognosis and inherent resistance to chemotherapeutics. Development and evaluation of new therapeutic approaches is highly needed. Immunosuppressant FTY720, approved for multiple sclerosis treatment, has recently raised attention for its anti-tumor activity in a variety of cancers. However, its therapeutic potential in MM has not been evaluated yet. METHODS: Cell viability and anchorage–independent growth were evaluated in a panel of MM cell lines and human mesothelial cells (HM) upon FTY720 treatment to assess in vitro anti-tumor efficacy. The mechanism of action of FTY720 in MM was assessed by measuring the activity of phosphatase protein 2A (PP2A)—a major target of FTY720. The binding of the endogenous inhibitor SET to PP2A in presence of FTY720 was evaluated by immunoblotting and immunoprecipitation. Signaling and activation of programmed cell death were evaluated by immunoblotting and flow cytometry. A syngeneic mouse model was used to evaluate anti-tumor efficacy and toxicity profile of FTY720 in vivo. RESULTS: We show that FTY720 significantly suppressed MM cell viability and anchorage–independent growth without affecting normal HM cells. FTY720 inhibited the phosphatase activity of PP2A by displacement of SET protein, which appeared overexpressed in MM, as compared to HM cells. FTY720 promoted AKT dephosphorylation and Bcl-2 degradation, leading to induction of programmed cell death, as demonstrated by caspase-3 and PARP activation, as well as by cytochrome c and AIF intracellular translocation. Moreover, FTY720 administration in vivo effectively reduced tumor burden in mice without apparent toxicity. CONCLUSIONS: Our preclinical data indicate that FTY720 is a potentially promising therapeutic agent for MM treatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12967-017-1158-z) contains supplementary material, which is available to authorized users.